Realizing Multicultural Education in History Learning: Strengthening Character to Increase National Competitiveness - Sariyatun Sariyatun; Abdul Rohman; Agus Mastrianto (Universitas Sebelas Maret, 2020)
Indonesia is a multicultural country that has various ethnicities, races, religions and cultures. However, the sense of mutual respect, respect and tolerance among Indonesians is now starting to diminish. This is of course a threat in itself for the Indonesian people, especially it will have an impact on the characteristics of the younger generation as the next generation who will determine the fate of the Indonesian people in the eyes of the world. Therefore, education is the main solution in dealing with these problems. Through multicultural education in history learning given in schools, it is hoped that a young generation of Indonesian character will emerge with character in order to increase the competitiveness of the Indonesian nation. This writing method uses a qualitative descriptive method. This writing aims to provide an idea or a new concept in the field of education, especially multicultural education in history learning in schools as an effort to strengthen the character of the nation. The conclusion of this writing is that through multicultural education in history learning, later we will have a young generation with character and uphold multicultural values. It is hoped that with this, the younger generation can be useful and participate in the efforts of the Indonesian people to face global competition in the international world.